Impact of Cancer Localization on Symptom Burden and Quality of Life in Head and Neck Cancers: A Comparative Study - Balk, Matthias; Rak, Atina; Rupp, Robin; Sievert, Matti; Müller-Hübner, Sarina Katrin Ursel; Koch, Michael; Iro, Heinrich; Gostian, Magdalena; Putz, Florian; Weissmann, Thomas; Allner, Moritz; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Background: Head and neck cancer (HNC) is a critical concern in oncology, with notable disparities in survival rates. While the long-term symptom burden in HNC survivors and its impact on quality of life (QoL) has been explored, there is limited understanding of the influence of cancer localizations on these aspects. This study aims to elucidate the role of cancer localizations in shaping long-term outcomes in HNC patients. Methods: A cross-sectional study was conducted at the University Hospital Erlangen’s Department of Otolaryngology, exploring the impact of cancer localization on symptom burden and QoL in 138 HNC patients using the University of Washington Quality of Life Questionnaire Version 4. Results: In our study of HNC patients, we investigated symptom burden across different cancer localizations, including oral cavity, oropharyngeal, hypopharyngeal, laryngeal, and cancer of unknown primary (CUP). While we found no significant variations in parameters such as pain, appearance, and activity, notable differences emerged in swallowing, speech, and salivation. Patients with oral cavity and laryngeal carcinomas had significantly higher swallowing and salivation scores compared to those with oropharyngeal carcinoma and CUP, while speech-related symptoms were lower for oral cavity and laryngeal carcinoma patients. Importantly, these symptom differences did not significantly impact health-related and overall QoL. These findings emphasize the nuanced interplay between symptomatology and QoL in different HNC cancer localizations. Conclusion: The research highlights significant disparities in post-treatment symptoms across different HNC localizations and underscores the need for personalized treatment and management strategies to address unique challenges associated with each HNC type, ultimately aiming to enhance post-treatment QoL.
CRIS-Team Scopus Importer:2024-11-08
Keywords: advanced-stage cancer; cancer; disease stage; early-stage cancer; follow-up; head and neck cancer; individualized care; patient-reported outcome; physical symptoms; psychological symptoms; quality of life; survivorship; symptom burden

Symptom Burden and Quality of Life in Long-Term Survivors with Head and Neck Cancer - Gostian, Magdalena; Allner, Moritz; Rak, Atina; Balk, Matthias; Rupp, Robin; Ostgathe, Christoph; Mantsopoulos, Konstantinos; Sievert, Matti; Iro, Heinrich; Hecht, Markus; Gostian, Antoniu-Oreste (Ent-Ear Nose & Throat Journal, 2024)
Objectives: In this study, long-term survivors of head and neck cancer (HNC) were evaluated regarding their symptom burden and quality of life (QoL). Methods: This prospective study was performed during the regular follow-up consultations at one of Germany’s largest tertiary referral centers for HNC. The assessment included demographic, clinical, and oncological data, as well as the MIDOS(2) and the University of Washington Quality of Life Questionnaire (UW QoL) questionnaires. Patients were subdivided based on their disease stage, that is, early cancer stages (UICC I/II) and advanced cancer stages UICC (III/IV). Results: Between January 1, 2019 and December 31, 2019, 212 HNC patients with a mean follow-up of 46.36 ± 43.64 months were included (120 patients UICC stage I/II (22.5% female, mean age 61.93 ± 12.38 years) versus 92 patients UICC stage III/IV (25.0% female, mean age 63.73 ± 11.74 years)). For all patients evaluated (UICC I/II versus III/IV), the three most common symptoms were tiredness (47.5 vs 60.9%, P =.073, r =.123), anxiety (35.8 vs 32.6%, P =.624, phi =.034) and drowsiness (35.0 vs 44.6%, P =.157, phi =.097). Patients diagnosed with UICC III/IV stages reported loss of appetite significantly more frequently and with a high level of severity (15.0 vs 32.6%, P =.002, phi =.157; 0.23 ± 0.60 vs 0.47 ± 0.78, P =.003, r =.203). The overall symptom burden was low with a severity sum score (min 0-max 30) of 3.04 ± 3.29 versus 3.58 ± 3.38 (P =.143, r =.100). All patients rated their QoL as good (65.67 ± 20.93 vs 59.56 ± 22.00, P =.043, r =.139). Conclusion: The overall symptom burden of long-term survivors of HNC is encouragingly low. Trial registration: The study was registered in the German Registry for Clinical Studies (application No.: 00017122). Date of registration: 15.08.2019. https://drks.de/search/de/trial/DRKS00017122.
CRIS-Team Scopus Importer:2025-02-04
Keywords: head and neck cancer; MIDOS(2); patient-reported outcome; quality of life; symptom burden; UW QoL